2000
DOI: 10.1159/000018309
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol Cream Combined with Twice Weekly Broad-Band UVB Phototherapy: A Safe, Effective and UVB-Sparing Antipsoriatric Combination Treatment

Abstract: Background: Calcipotriol has been combined with a number of systemic antipsoriatric treatments, improving efficacy or reducing the systemic treatment required. Although studies on calcipotriol and UVB have also been performed, there are no data on the UVB-saving effect of calcipotriol combined with broad-band UVB to reduce overall UVB exposure, while maintaining efficacy. Objectives: To assess the efficacy and safety of calcipotriol cream (50 μg/g) combined with twice weekly broad-band UVB and to determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 10 publications
1
43
0
2
Order By: Relevance
“…While Kragballe [18]described no significant difference in improvement between patients treated with topical calcipotriol in conjunction with UVB and those treated with calcipotriol alone, Kokelij et al [19]showed that the combination of calcipotriol and UVB light has been superior to monotherapy with UVB light. Ramsay et al [20]reported that the addition of calcipotriol cream to broad-band UVB treatment resulted in fewer UVB exposures and a lower cumulative irradiance. However, in our study there was no significant difference regarding therapy efficacy and treatment parameters in patients treated with either UVB monotherapy or UVB + adjunctive agents.…”
Section: Discussionmentioning
confidence: 99%
“…While Kragballe [18]described no significant difference in improvement between patients treated with topical calcipotriol in conjunction with UVB and those treated with calcipotriol alone, Kokelij et al [19]showed that the combination of calcipotriol and UVB light has been superior to monotherapy with UVB light. Ramsay et al [20]reported that the addition of calcipotriol cream to broad-band UVB treatment resulted in fewer UVB exposures and a lower cumulative irradiance. However, in our study there was no significant difference regarding therapy efficacy and treatment parameters in patients treated with either UVB monotherapy or UVB + adjunctive agents.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data were obtained from a Canadian study comparing calcipotriol and emollient in combination with broad-band UVB phototherapy [12]. In order to adapt to Dutch treatment settings, information of costs and current clinical practice of moderate to severe psoriasis were obtained by questionnaire to Dutch dermatologists, literature research and a consensus panel.…”
Section: Design and Methodsmentioning
confidence: 99%
“…The clinical trial involving 164 patients with moderate to severe psoriasis was conducted in nine centres in Canada [12]. The clinical study tested the efficacy and safety of calcipotriol combined with twice weekly UVB sessions compared to three weekly UVB sessions plus an emollient.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Several types of combination therapies have been proposed using vitamin D derivatives [24, 25, 26, 27]. They likely influence the histometric parameters used in the present study.…”
Section: Discussionmentioning
confidence: 99%